Effects of POH in Combination with STI571 on the Proliferation and Apoptosis of K562 Cells - 陈燕 胡东 (Current medical science, 2004)
The effects of monoterpene perilly alcohol (POH) alone or in combination with STI571 on the proliferation and apoptosis of the cell line K562 positive for Bcr/Abl were investigated. By using cell culture, the effect of the drugs on the proliferation of the cells was studied. TUNEL and flow cytometry assay of FITC-Annexin V and PI labeled cells were applied to detect the effects of the drugs on the apoptosis of the cells. The results showed that at 36 h, IC50 of POH on K562 positive for Bcr/Abl and HL-60 negative for Bcr/Abl were 81.0±11.3 μmol/L and 113.6±23.4μmol/L respectively (P>0.05). POH could inhibit the proliferation of K562 in a time and dosedependent manner with the inhibitory rate of 100 μmol/L POH on K562 cells at 36 h being (53.2±3.65)%. K562 cells were more sensitive to STI571 than POH. IC50 of STI571 on K562 cells in 36 h was (0. 256±0. 054) μmol/L. In a time and dose-dependent manner, POH induced the apoptosis of K562 cells with the percentage of apoptotic cells by 100 μmol/L POH at 40 h being (21.0±3.3)%. Both 100 μmo/L POH and 0.2 μmol/L STI571 had the same inhibitory effects on the K562 cells at 36 h. But at 12 and 24 h, the inhibitory rate of POH was significantly higher than that ofSTI571 (P~0.05) and the ability of STI571 inducing apoptosis at 36 h was greater than that of POH. 50 μmol/L, 100 μmol/L and 200 μmol/L POH in combination with 0.2 μmol/L STI571 could obviously increase the inhibitory effects on the cellular proliferation. Combined use of 50 μmol/L, 100 μmol/L, 200 μmol/L with 0.2 μmol/L STI571 could strongly induced apoptosis, es-pecially 200 μmol/L POH in combination with 0.2 μmol/L STI571. It was concluded that the antileukemia effect of POH had no obvious Bcr/Abl positive selectivity. POH can inhibit the proliferation of K562 and induce the apoptosis in a time- and dose-dependent manner. K562 cells were more sensitive to STI571 than POH. POH in combination with STI571 could obviously enhance the abilities of STI571 inhibiting the proliferation and inducing apoptosis of K562 cells.